The Use of Human Adipose-Derived Stem Cells in the Treatment of Physiological and Pathological Vulvar Dystrophies - Maria Giuseppina Onesti; Sara Carella; Simona Ceccarelli; Cinzia Marchese; Nicolò Scuderi (Hindawi Limited, 2016)
"Vulvar dystrophy" is characterized by chronic alterations of vulvar trophism, occurring in both physiological (menopause) and pathological (lichen sclerosus, vulvar graft-versus-host disease) conditions. Associated symptoms are itching, burning, dyspareunia and vaginal dryness. Current treatments often do not imply a complete remission of symptoms. Adipose-Derived Stem Cells (ADSCs) injection represents a valid alternative therapy to enhance trophism and tone of dystrophic tissues. We evaluated efficacy of ADSCs-based therapy in the dystrophic areas. From February to April 2013 we enrolled 8 patients with vulvar dystrophy. A biopsy specimen was performed before and after treatment. Digital photographs were taken at baseline and during the follow-up. Pain was detected with Visual Analogue Scale and sexual function was evaluated with Female Sexual Function Index. All patients received 2 treatments in 3 months. Follow-up was at 1 week , 1 and 3 months, and 1 and 2 years. We obtained a significant vulvar trophism enhancement in all patients, who reported pain reduction and sexual function improvement. Objective exam with speculum was easy to perform after treatment. We believe ADSCs-based therapy finds its application in the treatment of vulvar dystrophies, since ADSCs could induce increased vascularization due to their angiogenic properties and tissue trophism improvement thanks to their eutrophic effect.